2021
DOI: 10.21837/pm.v19i15.934
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Current Implementation of Compact and Mixed-Use Development Within Public Rail Transit Stations in Malaysia

Abstract: In the past years, the concept of Transit-Oriented Development has been adopted in cities and countries including Malaysia and Singapore. The integration of land use and public transport stations through Transit Oriented Development (TOD) as part of urban and cities strategy is highly acclaimed in promoting sustainable development concept in cities development. To understand the performance of TODs implementation in Klang Valley, this study has selected eleven stations in of Mass Rapid Transit (MRT) Putrajaya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The locations of Singapore's new town centers' rail transit stations have gradually developed into a particular TOD land use concept for Asian transit villages [ 27 ]. In Malaysia, to promote the idea of sustainable development in city development, Transit Oriented Development (TOD) integrates land use and public transportation facilities [ 28 ].…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…The locations of Singapore's new town centers' rail transit stations have gradually developed into a particular TOD land use concept for Asian transit villages [ 27 ]. In Malaysia, to promote the idea of sustainable development in city development, Transit Oriented Development (TOD) integrates land use and public transportation facilities [ 28 ].…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…To address the above questions, this study takes Shenzhen in China as a testbed. In Shenzhen, one of the most developed and compact cities, the TOD planning strategy has also emerged as a new, widely accepted idea for urban construction and urban rehabilitation (Niu et al, 2019;Ramlan et al, 2021;Renne & Appleyard, 2019). Therefore, a study in Shenzhen can help us understand the relationship between urban land and TOD construction to evaluate sustainable transportation planning for developed cities accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Transit-oriented development (TOD) is an urban planning concept that emphasised on integrating transport and land use planning in a way that promotes the use of public and active transportation over the use of the private motor vehicles (Curtis, Renne, & Bertolini, 2009;van Lierop, Maat, & El-Geneidy, 2017). Most of the TOD studies in local context are devoted to railway stations in urban areas (for example see Ramlan et al (2021), Yap et al (2021), Gomez et al (2019) and Woo (2020)), while suburban and rural stations are poorly investigated locally and even globally (Staricco & Vitale Brovarone, 2020). Although foreign studies have shown TOD adoption in suburban regions demonstrated a greater leap in the status quo as compared to its adoption in city centres (Sohoni, Thomas, & Rao, 2017), none of the local researcher attempt to focus on suburban or rural stations in studying TOD adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Although transit-oriented development (TOD) has recently emerged as a trending topic in both urban development policies and academic studies (Azmi et al, 2021;PLANMalaysia, 2021), most studies have not assessed the success of TOD adoption in a comprehensive manner. For instance, a recent study conducted by Ramlan et al (2021) solely focussed on "land-use diversity" principle in assessing the success of TOD adoptions. Meanwhile, Meng, Li, Taylor, and Scrafton (2021), Huang, Parker, and Minaker (2021) and Dong (2021) studies primarily emphasised on "demand management" principle.…”
Section: Introductionmentioning
confidence: 99%